2012
DOI: 10.1111/j.1365-2958.2012.08179.x
|View full text |Cite
|
Sign up to set email alerts
|

Double locking of an Escherichia coli promoter by two repressors prevents premature colicin expression and cell lysis

Abstract: SummaryThe synthesis of Eschericha coli colicins is lethal to the producing cell and is repressed during normal growth by the LexA transcription factor, which is the master repressor of the SOS system for repair of DNA damage. Following DNA damage, LexA is inactivated and SOS repair genes are induced immediately, but colicin production is delayed and induced only in terminally damaged cells. The cause of this delay is unknown. Here we identify the global transcription repressor, IscR, as being directly respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
2
36
0
1
Order By: Relevance
“…Interestingly, protein-mediated DNA precipitation has been reported in studies describing eukaryotic histones and the E. coli global regulator, protein HU, a known DNA-binding protein [13,14]. Operons, such as those of colicins, that encode proteins that can be detrimental to the producing cell are regulated precisely to ensure appropriate timing of synthesis and avoid untimely death of the producer [15-17]. We can thus speculate that synthesis of Usp and its associated Imu1-3 proteins could also be tightly regulated, limiting their production to avoid overt degradation and masking of the producers’ genome.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, protein-mediated DNA precipitation has been reported in studies describing eukaryotic histones and the E. coli global regulator, protein HU, a known DNA-binding protein [13,14]. Operons, such as those of colicins, that encode proteins that can be detrimental to the producing cell are regulated precisely to ensure appropriate timing of synthesis and avoid untimely death of the producer [15-17]. We can thus speculate that synthesis of Usp and its associated Imu1-3 proteins could also be tightly regulated, limiting their production to avoid overt degradation and masking of the producers’ genome.…”
Section: Resultsmentioning
confidence: 99%
“…The ssDNA is bound by the RecA protein forming a helical nucleoprotein filament. RecA nucleoprotein filaments at sites of DNA damage activate autocleavage of unbound LexA, provoking dissociation of LexA from SOS boxes to trigger expression of SOS genes [18].…”
Section: Lexa Regulates Colicin Synthesismentioning
confidence: 99%
“…Binding of two LexA dimers to overlapping LexA boxes is co-operative [21] and the two SOS boxes have been shown to effectively repress expression protecting the producer from overt lysis [22] and inhibit background levels of uninduced transcription [23]. A recent study showed that the association of LexA with a number of SOS operators tested was extremely rapid; however, LexA exhibited variable dissociation rates with significantly slower dissociation from the colicin K activity gene cka [18]. A highly conserved A tract is found in the dual-SOS boxes of bacteriocins at the distal and proximal LexA-binding sites.…”
Section: Lexa Regulates Colicin Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of the colicin operon is likely to be essential in determining the outcome of colicin-mediated competition, as the conditions under which colicin is produced and released govern the community dynamics. Recent findings suggest a link between nutrient conditions (exploitative competition) and colicin production and release (interference competition): production of colicins 1b, K, and the lysis protein of colicin E7, are controlled by nutrient-responsive regulators [11,32,33]. Environmental factors such as the type and amount of nutrients present in a habitat, may thus have a marked impact on colicin-mediated community dynamics and the persistence of biodiversity.…”
Section: Introductionmentioning
confidence: 99%